Application of Streptomyces Antimicrobial Compounds for the Control of Phytopathogens - Pacios-Michelena, Sandra; Aguilar González, Cristobal N.; Alvarez-Perez, Olga B.; Rodriguez-Herrera, Raul; Chávez-González, Mónica; Arredondo Valdés, Roberto; Ascacio Valdés, Juan A.; Govea Salas, Mayela; Ilyina, Anna (Frontiers in Sustainable Food Systems, 2021)
One of the relevant problems in today's agriculture is related to phytopathogenic microorganisms that cause between 30–40% of crop losses. Synthetic chemical pesticides and antibiotics have brought human and environmental health problems and microbial resistance to these treatments. So, the search for natural alternatives is necessary. The genus Streptomyces have broad biotechnological potential, being a promising candidate for the biocontrol of phytopathogenic microorganisms. The efficacy of some species of this genus in plant protection and their continued presence in the intensely competitive rhizosphere is due to its great potential to produce a wide variety of soluble bioactive secondary metabolites and volatile organic compounds. However, more attention is still needed to develop novel formulations that could increase the shelf life of streptomycetes, ensuring their efficacy as a microbial pesticide. In this sense, encapsulation offers an advantageous and environmentally friendly option. The present review aims to describe some phytopathogenic microorganisms with economic importance that require biological control. In addition, it focuses mainly on the Streptomyces genus as a great producer of secondary metabolites that act on other microorganisms and plants, exercising its role as biological control. The review also covers some strategies and products based on Streptomyces and the problems of its application in the field.